2011
DOI: 10.1152/physrev.00031.2010
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Types in Mammalian Skeletal Muscles

Abstract: Mammalian skeletal muscle comprises different fiber types, whose identity is first established during embryonic development by intrinsic myogenic control mechanisms and is later modulated by neural and hormonal factors. The relative proportion of the different fiber types varies strikingly between species, and in humans shows significant variability between individuals. Myosin heavy chain isoforms, whose complete inventory and expression pattern are now available, provide a useful marker for fiber types, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

89
2,465
7
45

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,313 publications
(2,704 citation statements)
references
References 889 publications
(823 reference statements)
89
2,465
7
45
Order By: Relevance
“…Diversity and plasticity of muscle-fibre types in pigs Muscle-fibre types can markedly vary in different species and muscle types, and are influenced by many factors such as sex and breed (Ryu et al, 2008), age, hormones and physical activity (Schiaffino and Reggiani, 2011). The variability of muscle fibres is due to the existence of multiple isoforms of each myofibrillar component (Clark et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Diversity and plasticity of muscle-fibre types in pigs Muscle-fibre types can markedly vary in different species and muscle types, and are influenced by many factors such as sex and breed (Ryu et al, 2008), age, hormones and physical activity (Schiaffino and Reggiani, 2011). The variability of muscle fibres is due to the existence of multiple isoforms of each myofibrillar component (Clark et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Human muscle fibers express three isoforms of myosin heavy chain (MyHC): MyHC-β, MyHC-2A, and MyHC-2X (respective genes MYH7, MYH2, and MYH1) (Schiaffino and Reggiani, 2011). The fourth isoform MHC-2B (MYH4) is not detected in humans.…”
Section: Fiber Type Comparisonmentioning
confidence: 99%
“…The muscle fibers that express MyHC-β are characterized as slow, fatigue resistant and oxidative (type 1 muscle fibers), whereas the fibers that express MyHC-2A are fast oxidative (type 2A muscle fibers), and the MyHC-2X fibers are fast glycolytic (type 2X muscle fibers). Most human muscles consist of all three muscle fiber types in varying degrees, depending on the functional demands of the muscle (Harridge, et al, 1996), age and gender (Schiaffino and Reggiani, 2011). Studies performed in rodents have demonstrated that MyHC isoforms expressed in differentiated myotubes were identical to the MyHC expression pattern in the muscle fibers from which the satellite cells were isolated (Dusterhoft andPette, 1993, Rosenblatt, et al, 1996).…”
Section: Fiber Type Comparisonmentioning
confidence: 99%
“…Although the skeletal muscle fibre‐type profile differs between murine and human skeletal muscle (myosin heavy chain isoform IIB is not expressed in humans),36 neuromuscular ageing in both humans and rodents share similar features. These include, but are not limited to, loss of muscle fibres37 and reduced myofibre CSA21, 38, 39 associated with degeneration and structural alterations of the NMJ,40, 41, 42 a decline in functional innervation (partial denervation)41, 43, 44 and loss of motor units 3, 44, 45.…”
Section: Introductionmentioning
confidence: 99%